Az 1941. júniusi magyar hadba lépés nemzetközi vonatkozásai = International aspects of Hungary entering the War in June, 1941 - Olasz, Lajos (Közép-Európai Közlemények, 2017)
After the Germans attacked the Soviet Union, extremely high internal and external pressure was put on the Hungarian government to join the war. The German diplomacy encouraged the Hungarian General Staff for voluntary participation only indirectly, while the German military leaders did it openly. The German economic, cultural, and minority organisations operating in Hungary, the SS, and the German intelligent service agents also urged Hungary to enter the war. Italy’s impatient behaviour, the rivalling neighbouring states (Romania, Slovakia, Croatia) joining the war, as well as the extensive European participation with voluntary troops had considerable impact on the government. All the above strengthened the fear in the Hungarian leadership that by keeping out they might lose the opportunity for further revision or they might even jeopardise the results achieved earlier. The air attack of Kassa (Kosice) gave the last push. Although the Hungarian government decided to enter the war on its own, in this decision international aspects greatly influenced it.